UJI PENGGUNAAN BERBAGAI MEDIA TUMBUH DAN PEMBERIAN PUPUK GROWMORE PADA AKLIMATISASI TANAMAN ANGGREK Dendrobium - GUSTI MARLINA; MARLINDA MARLINDA; HENI ROSNETI (Universitas Lancang Kuning, 2019)
The research objective was determine the effect of various growth media and growmore fertilizer on the acclimatization of Dendrobium orchids. study used a Completely Randomized Design (CRD) Factorial consisting of 2 factors, the first is (M) of growing media which consists of 3 levels, namely: M1 (medium fern root), M2 (wood charcoal medium), M3 (coir media coconut) and the second is (G) growmore fertilizer which consists of 4 levels, namely: G0 (without Growmore fertilizer), G1 (Growmore fertilizer 2 g / liter), G2 (fertilizer Growmore 4 g / liter), G3 (Growmore fertilizer 6 g / liter). Determine the growth of orchid plants, observations were made with the following parameters Growth Percentage (%), Plant Height (cm), Number of leaves (strands), and Number of tillers (stems). Data obtained were analyzed statistically, then continued with the Honestly Significant Difference Test (BNJ) at the level of 5%. The results showed that the single treatment of the use of growing media did not have a significant effect on the parameters of observation of growth percentage (%), plant height (cm), number of leaves (strands), and number of tillers (stems). The growth of growmore fertilizer also did not show a significant effect on the parameters of observation of growth percentage (%), plant height (cm), number of leaves (strands), and number of tillers (stems). Interaction of the use of various growth media and growmore fertilizer did not show a significant effect on the percentage of growth (%), plant height (cm), number of leaves (strands), and number of tillers (stems).